Social media and the reading culture revolution among digital natives - Dahlan, Dahlia (Universitas Ahmad Dahlan, 2022)
Reading is one of the intellectual activities that only humans have that develops along with the writing system. The culture of reading does not just grow, because human history records the development of the writing system through a very long journey. The study, which involved 41 respondents aged 17-21 years who were randomly selected, showed a shift in the reading culture from print media to online media, related to reading patterns, gender aspects, reading frequency, and duration. From a gender aspect. The shift in the reading culture among young people is also greatly influenced by the characteristics of online media that print media lacks. The practicality and mobility of online media as well as easy access are some of the advantages that attract young media users. Books, newspapers/tabloids, and magazines do not have this characteristic. required Greater effort is more expensive to access print media which is incompatible with the characteristics of the digital natives. Although it has a number of advantages, online media is still considered to have a number of weaknesses compared to print media. One of the weaknesses of online media is the inaccuracy of the information, because the writing often does not apply the principle of cross-checking and confirmation, and contains more subjective opinions.Â The survey results reinforce the tendency of new media audiences to be not merely positioned as objects that are the target of messages. The tendency to change in reading culture is closely related to audiences and changes in media technology and the meaning of media have renewed the role of audiences to become more interactive with messages, and new media consumers who are dominated by young people can determine how to access according to their wants and needs.